FORMATION OF PROFESSIONAL COMMERCIAL EDUCATION IN SIBERIA (1900–1919) - Tatyana A. Kattsina; Lyudmila E. Marinenko; Svetlana A. Lisina (Высшее образование в России)
The history of the origin and formation of professional commercial education in Siberia isconsidered while taking into account the impact of the capitalist development needs at the beginning of the XXth century. A number of quantitative and qualitative characteristics of professional commercial education in the Siberian region are suggested, with the focus on the regional specificity of its content. Introduction into the scientific use of published and unpublished (archival) sources could verify the existing positions (provisions) in the research literature on the progressiveness of the special commercial education.